Gender equality and inequalities in self-reported health in 27 European countries (2004 to 2016). (30th September 2020) - Roxo, L; Bambra, C; Perelman, J
Abstract: Background: Across Europe, women tend to report worse health than men, probably due to women's lower position in society. Although societal gender inequalities have decreased, differences persist regarding employment, income and use of time. This study aims to assess the evolution of gender-based inequalities in 27 European countries between 2004 and 2016, and to analyze the impact of societal gender equality in this evolution. Methods: We used data from the Survey on Income and Living Conditions (EU-SILC), from subjects between 25 and 64 years old (N = 2, 931, 081) from 27 European countries. Logistic regressions were performed with bad self-reported health as dependent variable, first adjusted for age, country and year, and later also for education and employment. Interactions between gender and year were added to the models to assess changes over time. Countries were clustered according to their societal gender equality, based on their Gender Equality Index of 2005 and 2015 (GEI). Analyzes were stratified by education, employment and cluster of GEI. Results: Women were 17% (OR = 1.17, 95%CI=1.15-1.19) more likely than men to report bad health. Considering education and employment, women were 3% less likely to report bad health (OR = 0.97, 95%CI=0.96-0.99). Gender-based inequalities were larger among the cluster with higher GEI (OR = 1.37, 95%CI=1.26-1.48) and those with lower education (OR = 1.21, 95%CI=1.18-1.24). Although the gender gap reduced from 26% (OR = 1.26, 95%CI=1.18-1.34) in 2004 to 16% (OR = 1.16, 95%CI=1.08-1.24) in 2016, the decrease was not significant. Differences between years were not significant when analyses were stratified for education, employment or cluster of GEI. Conclusions: Gender-based inequalities persisted between 2014 and 2016 and were strongly related to differences in education and employment. The gender gap was larger among countries with greater societal gender equality. Key messages: Women's disadvantage in self-reported health persisted in 2016 and was connected to socioeconomic differences. The gender gap is not smaller in countries with greater societal gender equality.